2019
DOI: 10.1155/2019/6057280
|View full text |Cite
|
Sign up to set email alerts
|

Comparing MicroRNA Profilings of Purified HER-2-Negative and HER-2-Positive Cells Validates miR-362-5p/Sema3A as Characteristic Molecular Change in Triple-Negative Breast Cancers

Abstract: Background. HER-2 is a key molecule serving as the therapeutic target, prognostic biomarker, and classification marker in breast cancer. Accurate microRNA profilings had not been conducted in purified tumor cells of HER-2-negative and HER-2-positive tissue specimens obtained from breast cancer patients. Methods. (i) Differential expression microRNA discovery using laser capture microdissection- (LCM-) assisted specimen preparation and microRNA array chips on HER-2 overexpressing and triple-negative breast carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The present study employed bioinformatics analysis to examine whether hsa_circ_0006620 acted with miR-502-3p, which we validated through luciferase report analysis. Former studies found that high miR-502-3p expression reduced migration, invasion, and proliferation abilities in different cancers, such as colorectal cancer, gastric cancer, osteosarcoma, breast cancers and lung cancers [16][17][18][19][20]. Previous study also found that miR-502 play an important role in the progress of prostate cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…The present study employed bioinformatics analysis to examine whether hsa_circ_0006620 acted with miR-502-3p, which we validated through luciferase report analysis. Former studies found that high miR-502-3p expression reduced migration, invasion, and proliferation abilities in different cancers, such as colorectal cancer, gastric cancer, osteosarcoma, breast cancers and lung cancers [16][17][18][19][20]. Previous study also found that miR-502 play an important role in the progress of prostate cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…EMT; cancer stem cell-like property; cytoskeleton reorganization [148,154] Cell proliferation, migration, and invasion [162] miR-155 TSPAN5 Promotion of stem cell proliferation and cellular proliferation [18,163] miR-150 [18] miR-142-5p miR-142-3p PTEN Cell proliferation and apoptosis [18,75,164,165] miR-135b…”
Section: Dnmt3bmentioning
confidence: 99%